Impact of Ornithine Decarboxylase on Semen Parameters and Functional Status of Spermatozoa in Type 2 Diabetes Mellitus - Malini, Dr. Suttur S. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: Type 2 diabetes mellitus (T2DM) represents a spectrum of metabolic disorders and affects all the physiological system including reproduction. Even though enormous research is carried out to focus the etiologies of infertility in T2DM, till date, the role of polyamines which modulate three multiple biochemical activities including nucleic acid and protein synthesis as well as cell signaling that are important for spermatogenesis are ignored. Limited studies are available on ornithine decarboxylase (ODC); an enzyme involved in the biosynthesis of polyamine and maintains the homeostasis of polyamines. Further, these studies are confined to animals only. Hence, an attempt was made to uncover the role of ODC in fertility of T2DM individuals. Materials and Methods: A total of 230 T2DM males and 50 control male subjects with proven fertility and non-diabetic aged between 25 and 50 years were recruited from different diabetic centers and clinics in and around Mysore, South India. Semen analysis and sperm function tests were carried out according to WHO guidelines. The level of ODC was estimated using enzyme-linked immunosorbent assay kit. Results: Our results demonstrate a strong association of type 2 diabetic conditions with reduced vitality of sperm, nuclear chromatin decondensation, and hypo-osmotic swelling among sperm function test along with a significant drastic reduction in the ODC levels. Reduced levels of ODC might be inadequate for homeostasis of polyamine. Conclusion: Overexpression of antizyme could have resulted in reduced level of ODC resulting in perturbation of normal spermatogenesis in T2DM individuals.